Perhitungan Struktur Komposit Pembangunan Ruang Kelas Baru Smp Negeri 44 Kecamatan Palaran Kota Samarinda - DAYAT, WI (KURVA S JURNAL MAHASISWA, 2014)
The process of a structure, a process that is focused and detailed, coherent, and repeatedly, in accordance with the function, layout, land-use of the building to be constructed. In the implementation in the field occurred several times repositioning time, so based on the layout of the building will affect the condition of the structural design of the building.Location development planning activities Negri Junior School Building 44 is located on the road Handil Palaran service districts. The collection of data obtained by data retrieval through secondary data is the data that is required to support primary data obtained from the literature, primary data is the collection of data obtained directly in the field.The contents of this thesis was to identify the multilevel structure calculations portal of reinforced concrete and structural elements in it with conventional mechanics calculation based on the SAP Program 2000 Version 14, the design and analysis of reinforced concrete structural components based on SNI 03-2847-2002.From the results of calculations performed by the authors obtained the calculation of reinforced concrete structures can be solved mengggunakan SAP Program 2000 Version 14, since SAP 2000 program is more practical than the other classical methods. As for the process design of reinforced concrete using the greatest moment values from the calculation on each rod which is reviewed by the SAP program, and also for the calculation of reinforced concrete structures it turns out there is little difference in the design of reinforced concrete beam as the dimensions and amount of reinforcement used.